2014
DOI: 10.1007/s00415-014-7605-3
|View full text |Cite
|
Sign up to set email alerts
|

Interleaved programming of subthalamic deep brain stimulation to avoid adverse effects and preserve motor benefit in Parkinson’s disease

Abstract: Subthalamic nucleus (STN) deep brain stimulation (DBS) is the most common surgical treatment for managing motor complications in Parkinson's disease (PD). Ultimately, outcomes depend on a variety of factors including lead location, access and expertize in programming and PD medical management. Nevertheless, achieving ideal programming settings can be difficult in certain patients, leading to suboptimal control of symptoms and stimulation-induced side effects, notably dysarthria and dyskinesia. Interleaved stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 10 publications
0
44
0
Order By: Relevance
“…An advantage of ILS stimulation is that 2 regions (e.g., STN and rZI) can be costimulated. With the exception of case reports, there are no large case series of ILS for the treatment of dyskinesias [20, 27-30]. The antidyskinetic effects of rZI stimulation evident in our study and reported in the literature may involve stimulation of the rZI and/or the surrounding pallidothalamic fibers.…”
Section: Discussionmentioning
confidence: 49%
“…An advantage of ILS stimulation is that 2 regions (e.g., STN and rZI) can be costimulated. With the exception of case reports, there are no large case series of ILS for the treatment of dyskinesias [20, 27-30]. The antidyskinetic effects of rZI stimulation evident in our study and reported in the literature may involve stimulation of the rZI and/or the surrounding pallidothalamic fibers.…”
Section: Discussionmentioning
confidence: 49%
“…[9] Furthermore, lower PPI is associated with increased distractibility, [9] and impairments have been linked to increased impulsivity and risk-taking behaviors. [28] Our study adds to the literature by showing that reduced PPI correlates with impulsivity in PD patients. However, despite the novelty of these present findings we acknowledge small sample size and possible epiphenomenon.…”
Section: Discussionmentioning
confidence: 57%
“…Interleaved stimulation allows for two programs to be used in an alternating fashion on the same lead and has been shown to reduce side effects. 28 Theoretically, interleaving shapes the current to reduce spread, whereas double monopolar stimulation spreads the current. This finding suggests that interleaved stimulation might reduce ICDs in PD.…”
Section: Discussionmentioning
confidence: 99%
“…ILS for DBS in the STN significantly improves PD symptoms and alleviates side effects. [2,6,7] One patient experienced improvements in symptoms of both PD and essential tremor after receiving ILS via a contact located in the STN and another in the ventrolateral anterior thalamus. [8] ILS is also used in patients with medication-refractory dystonia who are regarded as nonresponders to pallidal DBS, resulting in considerable improvement of dystonia with no side effects.…”
Section: Discussionmentioning
confidence: 99%